Private Capital Flows to Low Income Countries: Country-Specific Effects and the Lucas Paradox - Sweder van Wijnbergen; Corine Franken (Tinbergen Institute, 2010)
This paper analyses Net Private Capital Flows to LICs incorporating the recent surge in FDI between 2000 and 2006. We show that including country-specific effects in a paneldata setup resolves the Lucas Paradox, at least for LICs. Our results suggest that openness is among the most important factors explaining country-specific performance in attracting Net Private Capital Flows.
Keywords: F21; G15; 330; Private capital inflows; Low Income Countries; Lucas Paradox